G302 Adverse Drug Reactions in Nigerian Children. (7th April 2014) - Cliff-Eribo, K; Choonara, I; Sammons, H
Abstract : Aim: To describe reported adverse drug reactions (ADRs) for children in the Nigerian pharmacovigilance database. Nigeria has a population of 31 million children. Method: The analysis of reports for children aged 0 – 17 years submitted to the Nigerian pharmacovigilance centre from September 2005 to November 2012 was conducted. The data was analysed for number of reports, type of reporters, age and sex of patients. ADRs were classified according to system organ class and preferred terms, severity and outcomes. Results: A total of 297 reports were received during the period. For the first 4 years, <10 reports were submitted annually. From 2008, the number of reports has steadily increased to 182 in 2012. The reporting rate by 2012 was 5.9 reports per million children per year. Fifty two percent of the reports were for boys, and children aged 2 – 11 years had more reports (57%) than the other age groups. Pharmacists (49%) submitted more reports than physicians (22%) and other health professionals (23%). Antibiotics (23%), antimalarials (18%) and antivirals (12%) were the most commonly reported drugs. The most frequently reported ADRs were rash (16%), fever (10%), and pruritus (7%). 21 children died (8 from acute renal failure). Seven of the cases of acute renal failure were associated with substandard medicines used for teething problems. Diethylene glycol was identified as a contaminant in 4 of these cases and a further 3 were associated with calcium phosphate/coffee arabica/matricaria recutita/atropa belladonna, an herbal remedy. Fifteen children also experienced a variety of serious ADRs. Metamizole (dipyrone) was associated with 2 deaths and 2 serious ADRs. It was subsequently banned in 2005 in Nigeria. Four children experienced serious ADRs to the antimalarial, dapsone/chlorproguanil. Conclusion: The ADR reporting rate for children in Nigeria remains low compared to other countries; however, it has improved dramatically during the last three years. Some of the fatalities were associated with substandard medications. Concerted effort to check and limit these medications in the Nigerian market is recommended.